A Stressed Present and a Scared Future: An Autoethnography of a Migrant Scholar in Finland - Khan, Jawaria (Journal of International Students, 2022)
As an international doctoral researcher with a new-born daughter by my side, I reveal, in this autoethnography, the struggles to survive in the academic labor market of a non-Anglophone country, Finland. This personal narrative combined with sociological theory of Marxism brings a bottom-up perspective of international doctoral students. The purpose is to look inward and expose my vulnerable self that has been affected, moved and refracted by the academic neoliberalism causing alienation and my resistance. Explaining academic work as labor through vignettes, I present four cases of Marxist alienation that corelates with the alienation of early career researchers from the product (research output), process (doing research), species-essence (the passion of research) and other workers (academic colleagues). The findings of this autoethnography reiterates that academic labor is indeed in crisis. I recommend as researchers we should recognize this estrangement of academic labor and bring change through personal agency and ethical accountability.